May one murder the innocent for the sake of faith in God or filial piety to parents? A comparative study of Abraham's and Guo's stories. Issue 1 (2nd January 2017) - Liu, Qingping
ABSTRACT: Through a comparative analysis of the stories of Abraham and Guo, this article tries to argue that some particularistic claims of Christianity and Confucianism, which regard faith in God or filial piety to parents respectively as the sole ultimate principle of human life, may constitute the spiritual mainstay of such serious evils as murdering the innocent in certain in-depth paradoxes. Only by assigning a supreme position to their universal ideas of loving all humans through their self-transformations could the two ethico-religious traditions prevent those morally unacceptable evils motivated by their particularistic claims and overcome their in-depth paradoxes.